Science for all: Boosting the science motivation of elementary school students with utility value intervention. (April 2019) - Shin, Dajung Diane; Lee, Minhye; Ha, Jung Eun; Park, Jin Hyun; Ahn, Hyun Seon; Son, Elena; Chung, Yoonkyung; Bong, Mimi
Abstract: The need for students to learn science, technology, engineering, and mathematics (STEM) has increased steadily, while student motivation in this area continues to fall behind. We investigated the effects of science utility value intervention in increasing the science motivation (i.e., interest in science, appreciation of the role of science in future careers, and intention to engage in science-related activities) of Korean 5th and 6th graders. The usefulness of science for attaining the personal and communal goals inherent to various non-STEM careers was emphasized and internalized through classroom activities including postcard writing. At the end of the semester, students in the experimental group ( n = 219) perceived greater personal and communal utility in science than those from the control group ( n = 197). This enhanced perception of science utility led to greater interest, a higher likelihood of cognitively connecting science to future careers, and the willingness to engage in scientific activities. Highlights: Utility value intervention was implemented in elementary school classrooms. The usefulness of science literacy in popular non-STEM careers was emphasized. Students wrote about the usefulness of science for various jobs and communal goals. Intervention enhanced the personal and communal utility value of science. Intervention improved the willingness to engage in science-related activities.